Islamic Educational Thought Rooted in Banjar Local Wisdom: The Internalization of Baiman, Bauntung, Batuah, and Baadab Values in Qur'anic Memorization Education - Norhapijah; Zulfa Jamalie (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze Islamic educational thought rooted in Banjar local wisdom through the internalization of the values of Baiman, Bauntung, Batuah, and Baadab in Qur’anic memorization education. The study employs a qualitative approach using the library research method. Data were collected from books, scholarly journal articles, historical documents, and various relevant studies concerning Islamic education, Banjar culture, local wisdom, and Qur’anic memorization education. Data analysis was conducted through content analysis, interpretation, categorization, and synthesis of various academic sources. The findings reveal that Baiman serves as the foundation of spiritual and theological development, Bauntung represents educational productivity and competence, Batuah reflects beneficial character and social contribution, while Baadab embodies ethical and moral excellence. These values are not merely cultural expressions; rather, they constitute a comprehensive framework of Islamic educational thought that supports the holistic development of Qur’anic memorizers. The study further demonstrates that the integration of Banjar local wisdom into tahfidz education contributes to strengthening religious identity, character formation, and social responsibility. The novelty of this research lies in reconstructing Banjar cultural values as a conceptual framework of Islamic educational thought while positioning them as a foundational paradigm for contemporary Qur’anic memorization education